Fluorescent Canthin‐6‐one Alkaloids from Simaba bahiensis: Isolation, Identification, and Cell‐Labeling Properties. Issue 3 (11th February 2019) - dos Santos Costa, Rafael; do Espírito‐Santo, Renan Fernandes; Abreu, Lucas Silva; de Oliveira Aguiar, Leonardo; Leite Fontes, Dara; Fechine Tavares, Josean; Sobral da Silva, Marcelo; Botelho Pereira Soares, Milena; da Silva Velozo, Eudes; Flora Villarreal, Cristiane
Abstract: Canthin‐6‐one alkaloids, which are present in plants of the genus Simaba, are natural compounds that are capable of acting as fluorescent probes. However, the chemical composition and fluorescent properties of most species of this genus have not been analyzed. The objective of this study was to characterize the fluorescent properties of an extract of S. bahiensis and identify the chemical entities responsible for these properties. In addition, the cell‐labeling properties of the fluorescent dye fromA and of the isolated compounds were characterized by confocal fluorescence microscopy and flow cytometry. One quassinoid and three fluorescent alkaloids were isolated from S. bahiensis, all compounds were identified by using NMR spectroscopy and high‐resolution mass spectrometry. Staining experiments and HPLC‐FL analysis shown that canthin‐6‐one alkaloids are the main green fluorescent compounds in the analyzed dyes. All compounds evaluated showed a cytoplasmic marker with a residence time of 24 h. The present study is the first to describe the presence of canthin‐6‐one alkaloids in S. bahiensis, in addition to demonstrating promising cell‐labeling properties of fluorescent compounds from S. bahiensis with broad emission wavelengths. Abstract : Natural talent : Fluorescent Simaba bahiensis extracts and their component fluorescent compounds act as fluorescent markers in HEP‐G2 cells. The cell‐labeling profile, characterized using confocal microscopy and flow cytometry, shows that extracted and pure compounds act on cytoplasm regions, and kinetic evaluation shows that labeling persists for 24 h.